CIHR Canadian HIV Trials Network Coinfection and Concurrent Diseases Core: Canadian Guidelines for Management and Treatment of HIV/Hepatitis C Coinfection in Adults - Mark Hull; Marina Klein; Stephen Shafran; Alice Tseng; Pierre Giguère; Pierre Côté; Marc Poliquin; Curtis Cooper; on behalf of The CIHR Canadian HIV Trials Network HIV/Hepatitis C Management and Treatment Guidelines Working Group (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Hepatitis C virus (HCV) coinfection occurs in 20% to 30% of Canadians living with HIV, and is responsible for a heavy burden of morbidity and mortality. HIV-HCV management is more complex due to the accelerated progression of liver disease, the timing and nature of antiretroviral and HCV therapy, mental health and addictions management, socioeconomic obstacles and drug-drug interactions between new HCV direct-acting antiviral therapies and antiretroviral regimens.